2004
DOI: 10.1667/rr3219
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Lymphoma in AKR/J Mice does not Rise with Chronic Exposure to 50 Hz Magnetic Fields (1 μT and 100 μT)

Abstract: Some epidemiological studies suggest that exposure to 50 or 60 Hz magnetic fields might increase the risk of leukemia, especially in children with a comparable high residential exposure. To investigate this possibility experimentally, the influence of 50 Hz magnetic-field exposure on lymphoma induction was determined in a mouse strain that is genetically predisposed to this disease. The AKR/J mouse genome carries the AK virus, which leads within 1 year to spontaneous development of thymic lymphoblastic lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Median survival time was 183 (sham-exposed) and 190 days (exposed mice), and not significantly different according to the logrank test, with animals censored which were still alive at the end of the study. Patterns of tumor-related mortality in the sham-control group were consistent with those observed in a previous study conducted in this laboratory with AKR/J mice [32]. As seen in our previous study, essentially all mortality observed in AKR/J mice was related to the development of lymphoblastic lymphomas [33,34] (Figures 7, 8).…”
Section: Resultssupporting
confidence: 88%
“…Median survival time was 183 (sham-exposed) and 190 days (exposed mice), and not significantly different according to the logrank test, with animals censored which were still alive at the end of the study. Patterns of tumor-related mortality in the sham-control group were consistent with those observed in a previous study conducted in this laboratory with AKR/J mice [32]. As seen in our previous study, essentially all mortality observed in AKR/J mice was related to the development of lymphoblastic lymphomas [33,34] (Figures 7, 8).…”
Section: Resultssupporting
confidence: 88%
“…Three of the strains were not evaluated because of lymphoma development (AKR/J), confirming a well-documented strain specific phenotype, 70,71 lack of sufficient mice for analysis (CAST/EiJ), or self-mutilations resulting in euthanasia for humane purposes (SJL/J). Therefore, GWAS analyses were performed in 28 strains of mice.…”
Section: Methodsmentioning
confidence: 76%
“…76 All AKR/J mice died after the 12 months of age exclusively due to development of lymphomas, a known strain-specific lesion due to an endogenous retrovirus. 70,71 All AKR/J mice had structural abnormalities of their hair shafts, unrelated to age, due to a mutation in the Soat1 gene. 24,87 SJL/J fought extensively, especially, but not exclusively the males, requiring many to be euthanized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All AKR/J mice died prior to reaching this age and thus were necropsied at 12 months of age or in the longitudinal study. In the latter, AKR/J mice developed lymphomas, a known strain-specific lesion due to an endogenous retrovirus (43, 44). All AKR/J mice had structural abnormalities of their hair shafts, which were due to a mutation and unrelated to age (45, 46).…”
Section: Resultsmentioning
confidence: 99%